Carbon management index and chemical attributes of an Oxisol under different management systems - Schiavo, Jolimar Antonio; Rosset, Jean Sérgio; Pereira, Marcos Gervasio; Salton, Júlio Cesar (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate changes in the soil chemical attributes, carbon stock and in the C management index of a clayed Oxisol under different management systems. The soil under management systems with different historical usage was evaluated under the following covers: Zea mays, Urochloa decumbens, Panicum maximum cv. Tanzania. A cerrado area was used as check. Four composite samples were collected at 0–5, 5–10 and 10–20 cm soil depths. The phosphorus contents decreased with depth, and the higher values were observed in the area with P. maximum. In the area with Z. mays, higher values for K+, Ca++, Mg++, CEC, and base sum and saturation were observed. The total organic C content (TOC) was higher under cerrado vegetation cover, and smaller under P. maximum at 5–10 cm soil depth. The higher stocks of TOC, and of carbon in particulate fractions (C-POM) and in fractions associate to the soil mineral phase occurred in the area with U. decumbens, which promoted higher values for lability and C management indexes, similar to those for cerrado vegetation. In all coverings, the organic soil matter lability decreased with depth. The C-POM fraction had higher sensibility to variation in management practices, and is related to TOC.